1992
DOI: 10.1002/hed.2880140411
|View full text |Cite
|
Sign up to set email alerts
|

Papillary adenocarcinoma in thyroid hemiagenesis

Abstract: Variation in the gross anatomy of the thyroid gland is relatively common. Although thyroid hemiagenesis is felt to be a rare anomaly, its incidence is probably underestimated as the diagnosis is usually incidental. The case of a 41-year-old woman with right thyroid hemiagenesis associated with papillary adenocarcinoma is presented. The diagnosis of hemiagenesis was established by isotope imaging and surgical exploration for a benign nodule. Seven years later she was seen with a recurrent neck mass, and an isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
0
18
0
4
Order By: Relevance
“…Such disorders are Graves' disease [9,17,18,25,29,34,36,[44][45][46][47], chronic lymphocytic thyroiditis, subacute thyroiditis [24,48], nodular goiter [11,12,14,25,29,49], hyperfunctioning adenoma [10,15,45], and primary or metastatic carcinomas [6,7,11,19,23,25,26]. Hyperthyroidism was reported to be the major reason for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such disorders are Graves' disease [9,17,18,25,29,34,36,[44][45][46][47], chronic lymphocytic thyroiditis, subacute thyroiditis [24,48], nodular goiter [11,12,14,25,29,49], hyperfunctioning adenoma [10,15,45], and primary or metastatic carcinomas [6,7,11,19,23,25,26]. Hyperthyroidism was reported to be the major reason for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for the association between thyroid hemiagenesis and cancer, we found 15 patients (14 females and 1 male, mean age 48.57±15.9, range 14 to 74 years) 2,4,5,8,[10][11][12][13][14][15][16][17][18][19][20] (Table 3). Thyroid hemiagenesis was on the left in 8 cases (7 F and 1 M, mean age 50.5±17.1, range 14-69) and on the right in 6 (all women; mean age 47.8±16.5, range 30-74), while only one woman presented isolated isthmus absence.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that clinical symptoms of a thyrotoxic condition are more prominent than those of other thyroid conditions such as chronic thyroiditis (5-9) and thyroid carcinoma (1,11,12), and that the thyroid glands can be examined frequently in these patients. In 1994, Ozaki et al (3) reported that thyroid hemiagenesis was detected in seven out of 45,772 patients with Graves' disease (0.015%) in Ito Hospital (Tokyo).…”
Section: Discussionmentioning
confidence: 99%
“…It is usually detected only when the existing thyroid lobe is involved in other thyroid diseases such as Graves' disease (1-6), chronic thyroiditis (5-9), subacute thyroiditis (10) and thyroid carcinoma (4,11,12).…”
Section: Introductionmentioning
confidence: 99%